HSN1 VIRUS: A PANDEMIC THREAT - A. R. MALLICK; ABHERI DAS SARMA; A. K. GHOSH (International Journal of Pharma and Bio Sciences, 2010)
H5N1 is a subtype of the Influenza A virus. Not all H5N1 subtypes are the same. Some may be highly pathogenic while others cause mild disease of none at all in birds and so are called low pathogenic strains of the avian influenza virus. Viruses, by nature, change all the time and even a low pathogenic strain can turn into a highly pathogenic strain and vice versa. The highly pathogenic avian influenza virus subtype presently of global concern. Highly pathogenic bird flu (HPAI) is highly contagious disease affecting wild bird and poultry. There are three types of flu virus – A, B & C. Only types A & B Cause significant human disease. Flu A is further sub typed according to the type of protein (H) and (N) protein on its outer layer. There are 16 different H types (H1, H2 etc) and 9 different N types (N1, N2 etc). H5N1 viruses are spherically or longitudinally shaped enveloped particles with an up to eight-fold segmented, single-stranded RNA genome of negative polarity. H5N1 is a specific form that had not previously infected humans and is spreading rapidly amongst wild-bird populations. To avoid H5N1 infection one should strictly follow the precaution and preventive measures. Researchers across the world are trying to develop vaccines to check the pandemic threat that is rising in a tsunamic fashion.